Being First, Being Right, and Being Credible Since 2002: A Systematic Review of Crisis and Emergency Risk Communication (CERC) Research (Journal of International Crisis and Risk Communication Research, 2021)
The crisis and emergency risk communication (CERC) model is a five-stage theory that merges established public health practices with principles of crisis communication. Although CERC has been regularly applied on the ground, it has been criticized as lacking the coherence and unity necessary to serve as a framework for research. To determine the extent and type of research CERC has generated since its original presentation to the academic community 15 years ago, we conducted a systematic review of research using CERC as a theoretical lens. A total of 4,471 articles in 20 languages were screened, 400 full texts examined, and 19 articles included in the research and theory analysis, of which one tested tenets of the CERC model. We conclude that CERC has rarely been theoretically tested, and we argue that reformulation of the propositions is necessary for empirical support of the model to proceed.